Hubungan Perubahan Fisik Ruang dengan Kondisi Sosial Ekonomi Masyarakat di Kawasan Koridor Aglomerasi Mertoyudan, Kabupaten Magelang - Nursanti Anggraeni; Broto Sunaryo (Jurnal Wilayah dan Lingkungan, 2015)
Urban agglomeration is one of the factors that influence the development of Mertoyudan corridor. The research investigates the correlation of the physical change to socio-economic conditions of inhabitants in Mertoyudan corridor as the implications of urban agglomeration. A quantitative descriptive analysis applied by using crosstab analysis. The results show that the impact of agglomeration on the physical development is demonstrated by the high concentration of built-up area along Mertoyudan corridor. In addition, the change of livelihood from the agricultural sector to nonagricultural sector also increase and raising the income level of Mertoyudan corridor inhabitants. However, the urban agglomeration has the less impact to the mobility frequency and has no implication to the social interaction frequency because the urban agglomeration is still in initial phase. Therefore, this research suggests that there is a relationship between the physical aspect with some of the socio-economic variables, i.e. the land use change, livelihood change, and income level due to the urban agglomeration.